International Law in National Legal Systems: An Empirical Investigation. Issue 3 (July 2015) - Verdier, Pierre-Hugues; Versteeg, Mila
Abstract : International legal scholars have long recognized the importance of the rules and processes by which states adhere to international legal obligations and "translate" them into their domestic legal systems. Research by political scientists on specific issue areas likewise increasingly recognizes that domestic implementation is crucial to international law compliance and effectiveness. Yet the lack of systematic data makes it difficult to assemble an overall picture of the relationship between international law and domestic law around the world, let alone to document its evolution over time. Recent qualitative surveys of state practice have begun to fill that gap, but provide only a snapshot in time and are limited to relatively few countries. Some quantitative projects cover more countries, but address only a limited number of questions based solely on the text of national constitutions.